Factors related to osteoporosis preventive behaviors in middle age population - Chanapa, Patcharin; Maungrung, Monrudee; Manjaiwong, Darunee (Biomedical Sciences and Clinical Medicine, 2019)
Objective The purpose of this study were to examine factors related to osteoporosis preventive behaviors (OPPB) in the middle age population of Huay Yab, Ban Thi district, Lamphun Province. Methods The descriptive correlation study have been focused on 320 samples of age 35 to 59 years by stratified sampling. Data were collected by using structure interviews with questionnaires including the general profile, the knowledge of osteoporosis, the belief about osteoporosis, the self- efficacy on osteoporosis preventive behaviors, and the OPPB. The reliability and validity of questionnaires were tested and Cronbach’s alpha coefficients were obtained. The statistic analysis was performed by using Pearson’s product moment correlation coefficients and the Stepwise multiple regression analysis. Results Finding revealed that participants had a moderate level of osteoporosis knowledge and OPPB, the level of the belief about osteoporosis and the self- efficacy were high. The belief about osteoporosis, age, knowledge and hip fracture of family history were related to the OPPB (r=.401, r=.385, r= .185, r=.148, r=.140) respectively. The self- efficacy, gender, hip fracture of family history and body mass index (BMI) could together predict 32.2% of the variables in OPPB (p<0.01). Conclusion The self- efficacy , gender, hip fracture of family history and BMI were effected to OPPB, suggest that the interventions should aim at promoting those of factors to decrease osteoporotic fracture later in life.